Student Resilience against Exposure to Digital Radicalism: The Role of Islamic Religious Education Teachers and Progressive Rohis Extracurricular Activities - Rafa Salsabila; Taufik Sakni; Adi Putra (Edumaspul: Jurnal Pendidikan, 2024)
The proliferation of digital media has significantly shifted radicalization processes to online ecosystems, making adolescents highly vulnerable to extremist narratives. This study aims to analyze the synergistic roles of Islamic Religious Education (PAI) teachers and progressive Islamic spiritual extracurriculars (Rohis) in fostering student resilience against digital radicalism. Employing a narrative literature review approach, data were synthesized from peer-reviewed articles published in Google Scholar between 2019 and 2024. The findings reveal that combating digital extremism requires moving beyond restrictive measures toward building multidimensional cognitive, emotional, and social resilience. PAI teachers provide the essential theological foundation and digital literacy frameworks, while Progressive Rohis operationalizes these concepts through peer-led counter-narratives, inclusive social activism, and emotionally supportive environments. This collaborative mechanism effectively transforms students from passive consumers into active defenders of religious moderation. Ultimately, the study concludes that institutionalizing this educational synergy is crucial for policymakers to develop proactive, resilience-based strategies that empower youth to navigate the digital landscape safely and champion inclusive pluralism.